Aëtiana IV : papers of the Melbourne Colloquium on Ancient Doxography - Mansfeld, Jaap.; Runia, David T. (Philosophia Antiqua, 2018)
The articles collected here are based for the most part on papers read at the Colloquium "The Placita of Aëtius: Foundations for the Study of Ancient Philosophy," held in Melbourne in December 2015. The Placita , a first century CE collection of systematically organised tenets in natural philosophy ranging from first principles to human physiology is incompletely extant in several later sources. Its laborious reconstruction and the identity of its author are discussed from various angles. The text of the treatise is further elucidated by a novel statistical exploration of what is extant and what is missing. Its relation to various currents in the history of Greek philosophy and its reliability are also examined in some detail.